1981
DOI: 10.1353/aad.2012.1294
|View full text |Cite
|
Sign up to set email alerts
|

Creative Thinking and Dance/Movement Skills of Hearing-Impaired Youth: An Experimental Study

Abstract: Changes in creative thinking, as measured by Torrance's (1974) Thinking Creatively with Pictures, and in dance/movement skills were investigated in two groups of hearing-impaired students, aged 9-14. The experimental group (n=10) received 20 creative dance/movement lessons spaced over a 10-week period, whereas the control group (n=10) adhered to its regular school routine. Analysis of covariance showed that students given dance training improved significantly in originality, elaboration, total thinking creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
0
12
0
2
Order By: Relevance
“…A number of investigators have also found positive effects of dance programs in improving a variety of different developmental outcomes for special‐needs children (Caf, Kroflic & Tancig, 1997; Chamberlain‐Rickard, 1982; Jay, 1991; Reber & Sherrill, 1981). Jay (1991), for example, showed that a creative dance program positively affected creativity among a diverse group of preschool children with special needs (speech/language issues, behavior disorders and mental retardation).…”
mentioning
confidence: 99%
“…A number of investigators have also found positive effects of dance programs in improving a variety of different developmental outcomes for special‐needs children (Caf, Kroflic & Tancig, 1997; Chamberlain‐Rickard, 1982; Jay, 1991; Reber & Sherrill, 1981). Jay (1991), for example, showed that a creative dance program positively affected creativity among a diverse group of preschool children with special needs (speech/language issues, behavior disorders and mental retardation).…”
mentioning
confidence: 99%
“…The perception of inner rhythm helps in the comprehension and perception of exterior rhythm. The incentive to create an adapted rhythmic gymnastics program for the children with deafness was based on the fact that the rhythm of movement correlates with speech rhythm; thus, rhythmical education practices have a positive effect on the speech of children with deafness (19,24,31). Sherrill (25) suggested that in order for rhythm programs to be effective, they should be based on changes of various elements of rhythm, such as basic pulse, accentuation, rhythmic patterns, and musical phrase.…”
Section: Discussionmentioning
confidence: 99%
“…Dance is an ideal activity for the improvement of motor performance and self-concept of youth with hearing impairment (24), an indispensable tool that facilitates self-actualization, especially the awareness of the body with regard to appreciating its own ability for movement (19,31). Research has been conducted with regard to the psychological and cognitive aspects of individuals with hearing loss through the implementation of a dance program (2), and many schools have integrated dance into their curriculum as a means of enhancing body rhythm (2,5).…”
Section: Introductionmentioning
confidence: 99%
“…There are many known benefits from dancing, including artistic, educational, and therapeutic (Daley & Buchanan, 1999;Dinold, 2014;Hunter, 2013;Reber & Sherrill, 1981).…”
Section: Introductionmentioning
confidence: 99%